An Analysis of Plot In Hermann Hesse’s Novel Demian: The Story of Emil Sinclair’s Youth (ELang | An English Language Education Journal, 2018)
This research paper entitled An Analysis of Plot in Hermann Hesse’s Novel Demian: The Story of Emil Sinclair’s Youth. The novel has 8 chapters. It tells about ten years old boy, Emil Sinclair who feel different from his own family. He feel different from his sister, mother, and father who, in his opinion, were a part of a bright world, made out of kindness, order, morals, religious, and such things. The purpose of this research is to describe the plot and conflicts of the novel. The research method used in this research is descriptive. This method covers analyzing, describing and interpreting the data. After analyzing the data, the result of this research shows that the plot built in the right way. Every chapter contains the eight elements of plot which is covers of exposition, inciting force, conflict, rising action, crisis, climax, falling action, and resolution. The researcher also find out that the most conflict which is appear in the novel is Man vs Man with 87%, Man vs Self 87%, Man vs Society 50%, and the last one is Man vs God 25%. There is not conflict of Man vs Nature. In the end of research there are some suggestions for students of language program. Students should read literature, because by reading literature they can improve their competence of English language. For teacher, in teaching process the teacher can use a novel as their object of teaching. Because by reading novel students can improve their vocabulary mastery and reading comprehension. Students also gain a lot of knowledge and information by reading a novel, and also for the next researchers who analyze a novel should be more specific  to make the research easier to be analyzed.